Use of Pulse Pressure Variation as Predictor of Fluid Responsiveness in Patients Ventilated With Low Tidal Volume: A Systematic Review and Meta-Analysis (2020)
Introduction: Pulse pressure variation (PPV) has been shown to be useful to predict fluid responsiveness in patients ventilated at tidal volume (Vt) >8 mL kg−1. Nevertheless, most conditions in critical care force to use lower Vt. Thus, we sought to evaluate the operative performance of PPV when a Vt ⩽8 mL kg−1 is used during mechanical ventilation support. Methods: We searched PubMed and Embase databases for articles evaluating the operative performance of PPV as a predictor of fluid responsiveness in critical care and perioperative adult patients ventilated with tidal volume ⩽8 mL kg−1 without respiratory effort and arrhythmias, between January 1990 and January 2019. We included cohort and cross-sectional studies. Two authors performed an Independently selection using predefined terms of search. The fitted data of sensitivity, specificity, and area under the curve (AUC) were assessed by bivariate and hierarchical analyses. Results: We retrieved 19 trials with a total of 777 patients and a total of 935 fluid challenges. The fitted sensitivity of PPV to predict fluid responsiveness during mechanical ventilation at Vt ⩽8 mL kg−1 was 0.65 (95% confidence interval [CI]: 0.57-0.73), the specificity was 0.79 (95% CI: 0.73-0.84), and the AUC was 0.75. The diagnostic odds ratio was 5.5 (95% CI: 3.08-10.01, P < .001) by the random-effects model. Conclusions: Pulse pressure variation shows a fair operative performance as a predictor of fluid responsiveness in critical care and perioperative patients ventilated with a tidal volume ⩽8 mL kg−1 without respiratory effort and arrhythmias.